Increasing EFL Learner Participation through Eliciting Language: Insights from Conversation Analysis - Marco Cancino (National Research University Higher School of Economics, 2020)
The idea that interaction shapes learning in the second language classroom by increasing opportunities for participation, and that teachers can achieve this by adequately eliciting language from learners has been discussed in the literature. However, research specifying interactional resources deployed by teachers when eliciting language from their learners has been scarce. To this end, the present study used conversation analysis to examine the interactional resources produced in the elicitation of questions belonging to a specific lesson stage, namely, the 'classroom context mode' (CCM). In the CCM, fluency and meaningful exchanges are encouraged, and learners are prompted to talk about their feelings, emotions, and experiences, which represent a fruitful interactional juncture for eliciting learner language. The data collected in the present study come from four teachers and their students in an adult English as a foreign language (EFL) classroom at a language institute in Chile. The participants were audio-recorded over a total of six lessons that were delivered as part of a 10-week course. From the analysis, two novel elicitation resources, namely the 'effective management of closed questions' and the 'use of open referential questions as initiators of CCM', were found to promote a facilitator-oriented approach to teaching. The pedagogical value of these resources is discussed in terms of their potential for initiating and sustaining a CCM, and their inclusion in a framework that seeks to develop teachers' classroom interactional competence.